NUSYŪZ DALAM TINJAUAN PRINSIP HAM - Faiq Tobroni (Al-Maslahah : Jurnal Ilmu Syariah, 2020)
This paper aims to use human rights principles to reconsider nusyūz's arrangements in the Compilation of Islamic Law in Indonesian. This goal will be achieved by answering two questions, namely: what are the problems arising from the regulation of nusyūz? and why does the regulation need to be reviewed? This study uses a qualitative research method with a literature approach. Data obtained through documentation. This study found that the Compilation of Islamic Law actually narrowed the adoption of nusyūz only to wives, resulting in unequal relations which is gender biased. Shar'i arguments to expand the enactment of nusyūz can be obtained through a combination of An-Nisa 'Verses 34 and 128. In addition, it can be felt as a special paradigm of equality according to the human rights principles brought under Law 1/1974 and Law 32/2004. The concept of nusyūz which only applies to wives alone is a denial of the principle of equality in the concept of human rights, and also has weaknesses when juxtaposed with the concept of equality of husband and wife relations (Law 1/1974) and the concept of criminal liability that applies to both when doing violence (Law 32/2004).